2011
DOI: 10.1111/j.1467-8659.2011.02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent GPGPU Classification in Volume Visualization: A framework based on Error‐Correcting Output Codes

Abstract: In volume visualization, the definition of the regions of interest is inherently an iterative trial-and-error process finding out the best parameters to classify and render the final image. Generally, the user requires a lot of expertise to analyze and edit these parameters through multi-dimensional transfer functions. In this paper, we present a framework of intelligent methods to label on-demand multiple regions of interest. These methods can be split into a two-level GPU-based labelling algorithm that compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For both cases, the voxel feature set includes the voxel 3D coordinates, intensity, gradient magnitude and gradient along each of the three dimensions, defining an initial feature set for each voxel of eight features. These datasets have been used, among others, to test classification performance of different state‐of‐the art classifiers (such as AdaBoost [12]) in volume segmentation scenarios [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For both cases, the voxel feature set includes the voxel 3D coordinates, intensity, gradient magnitude and gradient along each of the three dimensions, defining an initial feature set for each voxel of eight features. These datasets have been used, among others, to test classification performance of different state‐of‐the art classifiers (such as AdaBoost [12]) in volume segmentation scenarios [18].…”
Section: Resultsmentioning
confidence: 99%
“…Basically, in this context the data entries x are the voxel's features (with W its associated codeword) and the possible classification labels correspond to the voxel's belonging to the different segmentation regions. In [18], the authors shown that using the Hamming distance (HD) metric [17] as the ECOC decoding measure has proven successful results in volume segmentation scenarios (Fig. 6).…”
Section: Mssl-bsm Framework Adaptation To Volume Segmentation Applicamentioning
confidence: 99%